Managing library resources in schools - Evans, Margaret Kinnell; Library Association (London : Library Association, 1994)
This book provides a guide on how schools can manage library resources to promote learning in their fold. Furthermore, it highlights relevant theory as a practical examples for the effective management of other learning resources.
Includes index.
Includes bibliographical references (p. [239]-243)
lje 22/1/19
Loans
Keywords: School libraries; Library resources; Library management